2017
DOI: 10.1155/2017/5739806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Serum Levels of Thyroid Hormones among Euthyroid Saudi Adults

Abstract: Aim of Study To assess serum thyroid hormones levels among Saudi adults and to correlate participants' serum levels with their grades of body mass index (BMI). Methodology A total of 278 adult subjects were recruited. Participants were categorized according to their BMI grades into normal weight (BMI < 25 kg/m2), overweight (BMI 25–29.9 kg/m2), or obese (BMI ≥ 30 kg/m2). Serum thyroid hormones levels were assessed at the central laboratory of Aseer Central Hospital, Abha City, by chemiluminescence immunoassay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
(33 reference statements)
0
17
2
Order By: Relevance
“…It has also been shown that hypothyroidism is more common among women with T2DM, compared to non-diabetic women [ 5 , 6 ], e.g., in a population-based prospective cohort study with 7.9-year follow up of 8452 individuals, hypothyroidism was reported as a risk factor for the incidence of T2DM, particularly among women with prediabetes [ 6 ]. Although the presence of T2DM and obesity was associated with the increased thyrotropin (TSH) concentration, the causal link between obesity and free triiodothyronine [FT3] and free thyroxin [FT4] is still under debate [ 7 , 8 ]. Therefore, it should be noted that the association of obesity and T2DM with hypothyroidism remains a gray area because subclinical hypothyroidism might well be secondary to obesity and T2DM [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that hypothyroidism is more common among women with T2DM, compared to non-diabetic women [ 5 , 6 ], e.g., in a population-based prospective cohort study with 7.9-year follow up of 8452 individuals, hypothyroidism was reported as a risk factor for the incidence of T2DM, particularly among women with prediabetes [ 6 ]. Although the presence of T2DM and obesity was associated with the increased thyrotropin (TSH) concentration, the causal link between obesity and free triiodothyronine [FT3] and free thyroxin [FT4] is still under debate [ 7 , 8 ]. Therefore, it should be noted that the association of obesity and T2DM with hypothyroidism remains a gray area because subclinical hypothyroidism might well be secondary to obesity and T2DM [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Solanki et al [ 32 ] and other authors [ 33 ] reported a significant positive association between participants’ BMI and their TSH mean serum levels, which was stated to suggest a state of possible sub-clinical hypothyroidism [ 15 ]. The association between TSH and BMI has been said to be under the influence of adipose tissue signals, and leptin has also been said to possibly have a significant effect on the central regulation of thyroid function through thyrotropin releasing hormone [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may have been responsible for the significantly higher T3/T4 ratio observed in obese children, which may be an indication of thyroid function and thyroid hormone action on tissues. Triiodothyronine plays very important and critical roles that influence body weight, and such roles include temperature homeostasis, resting energy expenditure (REE) by modulating the interaction with adipose tissue to influence the adaptations of metabolism, spontaneous motor activity and thermogenesis [ 34 ]. The T3/T4 ratio can be elevated in hyperthyroidism and hypothyroidism due to higher efficiency of the thyroid gland in secreting T3 as well as increased 5′ deiodinase tissue activity [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al-Musa correlated levels of serum thyroid hormones with body mass index (BMI) in 278 Saudi Arabian adults. 26 Slightly more than three-fourths of the study subjects were either overweight (31.3%) or obese (44.6%). Mean TSH serum levels showed a significant increase with increasing BMI, although T3 and T4 were not significantly related to BMI.…”
Section: Exposure To Chemicals Produced By Adipose Tissuementioning
confidence: 94%